Iqbal’s Inferences from the Qur’an: Objectives of Education for Developing the Individual Self (Journal of Education and Educational Development, 2020)
The Islamic Republic of Pakistan won its independence seventy years ago, yet its education system continues to be secular. If one of the main aims of education is to prepare the young generation for achieving national objectives, it is but imperative for Pakistan to design an education system from the Islamic perspective. Since Muhammad Iqbal is considered to be the ideologue of Pakistan and we find quite inclusive guidelines for developing a framework for an Islamic education system in Iqbal’s writing, it is imperative to explore his literature dealing with education. Two of his analogies Asrar e Khudi and Ramuz e Bikhudi are such works where we find Iqbal providing us with exhaustive recommendations for the same. The aims and directives for achieving goals of education were extracted from these two anthologies by employing qualitative method analysis and using hermeneutics approach under the supervision of a specialist on Iqbal. The results reveal that Iqbal’s concept and methodology of the development of self or individuality conformed to the approach of modern critics of contemporary education, who claim that the prevalent system is at odds with the natural human faculty of creativity.